(untitled) (Research, Society and Development, 2023)
Adsorption has been used in the treatment of wastewater for the removal of pollutants and has a low cost, requires low space for implementation and is simple to operate. When using biochar as an adsorbent material, adsorption becomes more sustainable, as it allows recycling of organic waste. This study aimed to investigate literature on the use of biochar as a pollutant adsorbent in wastewater, in order to verify its efficiency, application parameters and research gaps. Quantitative analysis was carried out, with articles’ categorization according to type of pollutant, year, and location of experiments. Therefore, qualitative aspects were analysed, such as pH, adsorption temperature, pyrolysis temperature, raw material and biochar activation, adsorption kinetics and isotherms, removal efficiency and adsorption capacity. It was observed that the studies are still recent, carried out in small scale and that researchers were typically concerned with the removal of emerging micropollutants. The most adopted pyrolysis temperature was between 400°C and 800°C and adsorption enhanced with increasing temperature by up to 45°C. The raw materials used were diverse and they were usually available in the study region. Moreover, biochar showed greater efficiencies when activated. The pseudo second order kinetic model and the Langmuir isotherm were the ones that best fit most of the experiments. Finally, research gaps were identified concerning economic aspects, regeneration and discharge processes of biochar, and efficiency with non-synthetic effluents.